2020
DOI: 10.1093/pm/pnaa342
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ultrasound-Guided Percutaneous Electrolysis for Musculoskeletal Pain: A Systematic Review and Meta-Analysis

Abstract: Objective To evaluate the effects of ultrasound-guided percutaneous electrolysis alone or as an adjunct to other interventions on pain and pain-related disability for musculoskeletal pain conditions. Databases and Data Treatment Search of MEDLINE database, Allied and Complementary Medicine Database, EMBASE database, Cumulative Index to Nursing & Allied Health Literature database, EBSCO database, PubMed database, Physiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…One of the hypotheses currently handled in publications [22] investigating evident clinical effects of electrolysis, is the clearing of algogenic and inflammatory substances that have been found in degeneration tendon areas and its periphery at initial stages of tendon degeneration. In a recent systematic review, Gomez-Chiguano et al [23] presented results of moderate scientific evidence of electrolysis for the treatment of pain and musculoskeletal dysfunction. For this reason, the aim of our study was to determine the effects of a new treatment with percutaneous electrolysis directed to peripheral tendon, with or without the presence of degenerative zone.…”
Section: Introductionmentioning
confidence: 99%
“…One of the hypotheses currently handled in publications [22] investigating evident clinical effects of electrolysis, is the clearing of algogenic and inflammatory substances that have been found in degeneration tendon areas and its periphery at initial stages of tendon degeneration. In a recent systematic review, Gomez-Chiguano et al [23] presented results of moderate scientific evidence of electrolysis for the treatment of pain and musculoskeletal dysfunction. For this reason, the aim of our study was to determine the effects of a new treatment with percutaneous electrolysis directed to peripheral tendon, with or without the presence of degenerative zone.…”
Section: Introductionmentioning
confidence: 99%
“…One needling intervention that is commonly US-guided is percutaneous electrolysis, an intervention consisting of the application of a galvanic electrical current throughout a filament needle. A recent meta-analysis found moderate evidence suggesting a positive effect of US-guided percutaneous electrolysis for pain and related disability in patients with musculoskeletal pain [ 13 ]. Further, an animal study has observed that the application of percutaneous electrolysis can release nerve tissue, i.e., the sciatic nerve, from a fibrous entrapment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although scientific evidence concerning PE is still limited compared to other physical therapies, the number of publications investigating the effectiveness of this treatment is progressively growing [ 6 , 7 ]. The efficacy of this technique has been mainly studied in musculoskeletal disorders; in fact, a recent meta-analysis has found moderate evidence suggesting a positive effect of PE for reducing pain and related disability in these pathologies [ 8 ]. Some of the conditions that could benefit from PE treatment are patellar tendinopathy, lateral epicondylalgia, shoulder pain, whiplash syndrome, or temporomandibular pain [ 4 , 6 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the conditions that could benefit from PE treatment are patellar tendinopathy, lateral epicondylalgia, shoulder pain, whiplash syndrome, or temporomandibular pain [ 4 , 6 , 9 , 10 , 11 , 12 , 13 ]. However, which musculoskeletal pain conditions would receive the greatest benefit from this approach and the ideal dosage are questions still unanswered [ 8 ].…”
Section: Introductionmentioning
confidence: 99%